2015
DOI: 10.1190/geo2014-0509.1
|View full text |Cite
|
Sign up to set email alerts
|

On the specific polarizability of sands and sand-clay mixtures

Abstract: The concept of specific polarizability [Formula: see text], being the ratio between imaginary conductivity and specific surface area, can be used to represent the polarization of the mineral-fluid interface per unit pore-volume-normalized surface area [Formula: see text] and to account for the control of the fluid chemistry and/or mineralogy on induced polarization (IP) measurements. We used a database of IP measurements on sands and sand-clay mixtures to investigate the variation in [Formula: see text] as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 16 publications
2
37
2
Order By: Relevance
“…We observed the same trend for mica‐rich sands in our data. For quartz‐clean sands, Weller et al () observed a lower Cp value (5.8 × 10 −12 S), which in our case is replicated by the glacial sands showing lower Cp values, although they are not as uniform as the laboratory sands. Overall, the estimated σmax deviates from CpSpor less than 1 order of magnitude for most of the samples, suggesting that estimates of permeability within 1 order of magnitude can be expected from IP data in this study.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…We observed the same trend for mica‐rich sands in our data. For quartz‐clean sands, Weller et al () observed a lower Cp value (5.8 × 10 −12 S), which in our case is replicated by the glacial sands showing lower Cp values, although they are not as uniform as the laboratory sands. Overall, the estimated σmax deviates from CpSpor less than 1 order of magnitude for most of the samples, suggesting that estimates of permeability within 1 order of magnitude can be expected from IP data in this study.…”
Section: Resultssupporting
confidence: 73%
“…The relationships derived from their laboratory measurements for different Cp values are shown for reference in Figure d. Weller et al () found that sand mixed with muscovite and illite, has a higher Cp value (24 × 10 −12 S) than the common value of Cp (10 × 10 −12 s) suggested by Weller et al (). We observed the same trend for mica‐rich sands in our data.…”
Section: Resultsmentioning
confidence: 93%
“…Weller et al . () show that interlayer spaces in swelling clay minerals may contribute to the polarization in sand–clay mixtures, where small amounts of clay minerals (up to 1.9 weight %) are dispersed in the sample. The distribution of clay minerals in the sample (connected or dispersed) seems indeed to be a critical factor regarding whether these clay minerals will contribute to polarization or not (Osterman et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is also suggested that the presence of clay minerals may cause an increase in polarization effects, in addition to an increased surface conductivity (Vinegar and Waxman ; Weller et al . ; Leroy et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation